EKSPLORASI ETNOMATEMATIKA PADA KUE LUMPUR DI PASAR GONDANGLEGI - Kurniati, Rina; Handayani, Ucik Fitri (Al-'Adad: Jurnal Tadris Matematika, 2025)
This study aims to explore ethnomathematics concepts in "kue lumpur" (mud cake) sold at Gondanglegi Market, Malang. The research employs an ethnographic method with a qualitative approach. Data were collected through observations, interviews, and documentation, focusing on mathematical elements found in the shape and production process of "kue lumpur." The results reveal that the cake contains geometric concepts, such as circular shapes and their properties, as well as the concept of a system of linear equations with two variables (SPLDV) related to raw materials, production quantity, costs, and profits. This study emphasizes the importance of integrating local culture into mathematics education through ethnomathematics to provide more relevant and applicable learning experiences for students while preserving cultural heritage